(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Catering is a business that provides service to an event or location. A catering proposal will generally include the rental of the venue, transport, equipment, arrival time, staff arrival time, bar open and close time, mealtime, and rental pick up. Given that catering services are one of the prominent and profitable businesses in the hospitality industry, the researchers planned to establish a catering business under a general partnership. Chasing Perfection, which is the business name, came up with a starting capital of 1 million pesos, which is sufficient enough to sustain its operating expenses. Chasing Perfection provides services for weddings, anniversaries, birthdays, baptismal, corporate activities, and other events. The researchers used a survey questionnaire with a set of questionnaires including questions about the demographic profile of the respondents and the business. Random people were surveyed to get their suggestions and opinions about the products. The results of the survey signified great potential for the business to pursue and become successful in the future. Meanwhile, the results of the study revealed that 68% of 50 respondents were more interested in catering services. The survey also revealed that 42% of the respondents were housewives possibly as they are more hands-on regarding arranging occasions or events. Cake was the most favorable dessert according to 46% of the respondents. Regarding advertising, 74% of the respondents prefer to have it on social media for convenience and easy access. Loot bags are the most preferred give-a-ways, while online booking was the most preferred contact point of every client reaching for catering services. The study proved that Chasing Perfection is acceptable. The finished products and services are feasible for business gradually and progressively. In terms of management viability, Chasing Perfection can generate the product properly and take the possible opportunity to handle the business with excellent service by controlling all situations on the management and thinking of the best way to secure and handle the business. Overall, the financial viability of Chasing Perfection is determined by the income, operating payments, and debt commitment.